Synthesis and crystal structure of (S,E)-4-hydroxy-3-(2-((4aR,6aS,7R,10aS,10bR)-3,3,6a,10b-tetramethyl-8-methylenedecahydro-1H-naphtho[2,1-d][1,3]dioxin-7-yl)ethylidene)dihydrofuran-2(3H)-one, C23H34O5 - Li Shi-Qing; Zhou Jian; Dong Zhang-Chao; Pan Bo Wen; Shi Yang; Zhou Ying (Zeitschrift für Kristallographie - New Crystal Structures)
C23H34O5, orthorhombic, P212121 (no. 19), a = 11.1838(3) Å, b = 11.7824(3) Å, c = 16.3160(5) Å, V = 2149.99(10) Å3, Z = 4, Rgt ${R}_{gt}$ (F) = 0.0399, wRref $wR_{ref}$ (F 2) = 0.1097, T = 293 K.